Effect of IGF1, GH, and PIT1 markers on the genetic parameters of growth and reproduction traits in Canchim cattle - Grossi, Daniela do Amaral; Buzanskas, Marcos Eli [UNESP]; Grupioni, Natalia Vinhal [UNESP]; Paro de Paz, Claudia Cristina; Almeida Regitano, Luciana Correia de; Alencar, Mauricio Mello de; Schenkel, Flavio Schramm; Munari, Danisio Prado [UNESP] (Springer, 2015)
The availability of dense genomic information has increased genome-wide association studies for the bovine species; however research to assess the effect of single genes on production traits is still important to elucidate the genes functions. On this study the association of IGF1, GH, and PIT1 markers with growth and reproductive traits (birth weight, weaning weight, weight at 12 and 18 months of age, preweaning average daily weight gain, age and weight at first calving, and scrotal circumference at 12 and 18 months of age) were assessed by means of the variance component approach. The phenotypes were adjusted and then analyzed under two animal models, one which considered the polygenic and genotype (IGF1, GH or PIT1 markers) effects (Model 1), and the other which considers only the polygenic effect (Model 2). When the likelihood ratio test and the Bonferroni correction was applied at 5 % significance level, the genetic markers for the IGF1, GH, and PIT1 genes did not influence significantly the traits (p > 0.002). However, evidence of association of IGF1 with birth weight (p = 0.06) and GH with weight at first calving (p = 0.03) and with weight at 12 months of age (p = 0.08) was observed. In conclusion we could not confirm the associations between IGF1, GH, and PIT1 and growth traits that were previously reported in Canchim cattle, and no association was observed between these genes and reproductive traits. Future studies involving functional markers of IGF1, GH and PIT1 genes may help to clarify the role of these genes in growth and reproductive processes.
Keywords: Association analysis; Candidate genes; Identity by descent matrix; Quantitative trait loci